Apa yang mempengaruhi kinerja aparatur Pemerintah Daerah? - Adhivinna, Vidya Vitta; Dinuriah, Aulia Syahadatun (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2020)
This study aims to determine the effect of budget participation, organizational commitment, and public accountability on regional government apparatus' performance. The population in this study were employees of Kulon Progo Regional Organizations. The number of samples used in this study was 96 respondents with the method of determining the sample using the purposive sampling method. The data were analyzed with multiple linear regression to test the hypotheses. The result of this study indicates that budget participation and public accountability have a significant impact on the employee's performance of regional government, and organizational commitment does not significantly affect local government apparatus' performance.